Lost and found family : a novel - Ryan, Jennifer, 1973- (William Morrow, an imprint of HarperCollinsPublishers, 2021)
Sarah Anderson decides that it is finally time to reveal the truth about her seemingly perfect late husband so that she can move on with her life, and, in losing the past, finds a new love -- and family.